Answer:
A, C, D, F
Step-by-step explanation:
Given the expression : (3/5)³
Recall :
a^b where, a = base ; b = exponent
In ; (3/5)^3
Base = 3/5 ; exponent = 3
Similarly ;
a^b = a in b places
(3/5)^3 = (3/5) * (3/5) * (3/5)
(3/5) * (3/5) * (3/5) = (3*3*3) / (5*5*5) = 27/125
Hence, A, C, D and F are all correct
The answer is A. Here's the equation graphed and shows why the answer is A
Answer:
291 .1
Step-by-step explanation:
80.2 + 91.6 + 123 + 204.7 + x = 790.6
790.6 - 499.5 = 291. 1
Answer:
f(x) = -(x-3)^2 + 4
Step-by-step explanation:
(h; k) are the coordinates of the vertex.
On the graph are (3, 4), therefore we have:
f(x) = a(x-3)^2 + 4
We have the x- intercept (1,0) -> x=1; y=0.
Substitute them into the equation:
0 = a(1 - 3)^2 + 4
0 = a(-2)^2 + 4
4a + 4 = 0 | -4
4a = -4 |-4
a = -1
So, we have the answer:
f(x) = -(x-3)^2 + 4
Answer:
x = 42
Step-by-step explanation:
The marked angles are supplementary, so their sum is 180°.
(2x +8) +(2x +4) = 180
4x +12 = 180 . . . . . . . . . simplify
x +3 = 45 . . . . . . . divide by 4 (because we can)
x = 42 . . . . . . subtract 3
_____
<em>Additional comment</em>
A "two-step" linear equation like this one is usually solved by subtracting the unwanted constant, then dividing by the coefficient of the variable. Here, we have done those steps in reverse order. This makes the numbers smaller and eliminates the coefficient of the variable. Sometimes I find it easier to solve the equation this way.